2021
DOI: 10.1063/5.0038588
|View full text |Cite
|
Sign up to set email alerts
|

Strain-controlled electrical and magnetic properties of SrRuO3 thin films with Sr3Al2O6 buffer layers

Abstract: SrRuO3 (SRO) thin films have been grown on a (001)-oriented SrTiO3 substrate with Sr3Al2O6 (SAO) buffer layers using pulsed laser deposition. X-ray diffraction results reveal that the epitaxial strain of SRO changes from compressive to relaxed or tensile ones by tuning the thickness of the SAO buffer layer (tSAO). We have demonstrated that the variation of strain has a strong influence on the microstructure and electrical and magnetic properties of SRO. When tSAO < 10 nm, the epitaxial strain is relaxed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The theoretical work has also shown that the inherent epitaxial strain could inhibit the overall exchange interactions in LSMO, thus prompting the epitaxial film to be antiferromagnetic and insulating . To overcome the epitaxial strain at the interface and eliminate dead layers of the LSMO films grown on LAO substrates, the strategy of inserting a buffer layer, e.g., STO and LaMnO 3 , between films and substrates was shown as a viable route. ,, Sr 3 Al 2 O 6 (SAO) has a highly efficient strain-relaxing capacity, which has also been recently shown to be an excellent buffer layer to tune magnetic and electrical properties of correlated oxides. , The increased distance between (Al 6 O 18 ) 18– clusters and Sr 2+ ions leads to the weaker Coulomb interaction between them, which makes the elastic modulus of SAO 50–60% less than that of STO, allowing the easy control of the dead layers with less thickness. ,, In addition, SAO is water-soluble and can serve as a sacrificial layer for transferring a freestanding LSMO membrane, which is promising for flexible and wearable device applications. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical work has also shown that the inherent epitaxial strain could inhibit the overall exchange interactions in LSMO, thus prompting the epitaxial film to be antiferromagnetic and insulating . To overcome the epitaxial strain at the interface and eliminate dead layers of the LSMO films grown on LAO substrates, the strategy of inserting a buffer layer, e.g., STO and LaMnO 3 , between films and substrates was shown as a viable route. ,, Sr 3 Al 2 O 6 (SAO) has a highly efficient strain-relaxing capacity, which has also been recently shown to be an excellent buffer layer to tune magnetic and electrical properties of correlated oxides. , The increased distance between (Al 6 O 18 ) 18– clusters and Sr 2+ ions leads to the weaker Coulomb interaction between them, which makes the elastic modulus of SAO 50–60% less than that of STO, allowing the easy control of the dead layers with less thickness. ,, In addition, SAO is water-soluble and can serve as a sacrificial layer for transferring a freestanding LSMO membrane, which is promising for flexible and wearable device applications. , …”
Section: Introductionmentioning
confidence: 99%
“…32,40,41 Sr 3 Al 2 O 6 (SAO) has a highly efficient strainrelaxing capacity, which has also been recently shown to be an excellent buffer layer to tune magnetic and electrical properties of correlated oxides. 42,43 The increased distance between (Al 6 O 18 ) 18− clusters and Sr 2+ ions leads to the weaker Coulomb interaction between them, which makes the elastic modulus of SAO 50−60% less than that of STO, allowing the easy control of the dead layers with less thickness. 42,44,45 In addition, SAO is water-soluble and can serve as a sacrificial layer for transferring a freestanding LSMO membrane, which is promising for flexible and wearable device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the sacrificial layer is of paramount importance. Its crystal structure, chemical composition, surface morphology, and lattice parameter will affect the crystalline quality of the transferred film and the selective etching. (La,Sr)­MnO 3 (LSMO), SrRuO 3 (SRO), and Sr 3 Al 2 O 6 (SAO) are some of the sacrificial layers used to prepare epitaxial perovskite oxide membranes such as SrTiO 3 , BiFeO 3 , , BaTiO 3 , BaSnO 3 , SRO, , and LSMO or even nanocomposites BaTiO 3 –CoFe 2 O 4 . Among the above-mentioned sacrificial layers, SAO is especially suitable to prepare perovskite oxides, it can be easily dissolved in water, contributing to the sustainability of the process, and by scrupulous variation of its lattice constant via cation substitution permits easy lattice matching with the functional oxide and avoid further crack formation. ,, Nonetheless, the soft and open structure of SAO has a strong sensitivity to air humidity and can also facilitate cation interdiffusion during the high-temperature growth of the targeted complex oxide film. ,, These characteristics can jeopardize the quality of the oxide membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Thus this freestanding treatment of a single-crystalline TMO thin lm enables us to obtain a exible membrane that can be stacked or squeezed by a well-designed transfer and most importantly shed light on the possible surface area enlargement for a substantial enhancement of electrochemical catalysis. In addition, freestanding TMO also allows us to arti cially manipulate the strain condition [24][25][26] . SrRuO 3 (SRO) is an OER active transition metal oxide, and the electronic structure of SRO is sensitive to the strain condition which can trigger a high spin state for lowering the adsorption energy between SRO and oxygen intermediates [27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%